Construction of human induced pluripotent stem cell‐derived oriented bone matrix microstructure by using in vitro engineered anisotropic culture model - Ozasa, Ryosuke (J Biomed Mater Res A, 2017)
Bone tissue has anisotropic microstructure based on collagen/biological apatite orientation, which plays essential roles in the mechanical and biological functions of bone. However, obtaining an appropriate anisotropic microstructure during the bone regeneration process remains a great challenging. A powerful strategy for the control of both differentiation and structural development of newly‐formed bone is required in bone tissue engineering, in order to realize functional bone tissue regeneration. In this study, we developed a novel anisotropic culture model by combining human induced pluripotent stem cells (hiPSCs) and artificially‐controlled oriented collagen scaffold. The oriented collagen scaffold allowed hiPSCs‐derived osteoblast alignment and further construction of anisotropic bone matrix which mimics the bone tissue microstructure. To the best of our knowledge, this is the first report showing the construction of bone mimetic anisotropic bone matrix microstructure from hiPSCs. Moreover, we demonstrated for the first time that the hiPSCs‐derived osteoblasts possess a high level of intact functionality to regulate cell alignment. © 2017 The Authors Journal of Biomedical Materials Research Part A Published by Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 360–369, 2018.